1994
DOI: 10.1159/000133676
|View full text |Cite
|
Sign up to set email alerts
|

A mammalian homologue of Drosophila heterochromatin protein 1 (HP1) is a component of constitutive heterochromatin

Abstract: The Drosophila HP1 gene contains a highly conserved sequence, the chromobox, which can be used to isolate HP1-like genes from both mouse (M31 and M32) and man (HSM1) (Singh et al., 1991). Here we report that a monoclonal antibody (MoAb) raised against the M31 protein recognises a 26-kDa protein in murine and human nuclear extracts and localises to large masses of condensed chromatin within murine interphase nuclei, some of which are associated with the nucleoli. At metaphase, the MoAb binds to the centromeres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
152
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(167 citation statements)
references
References 0 publications
10
152
3
Order By: Relevance
“…Expression of all transfected proteins (full-length and truncated HP1) was detectable 12 h after transfection using an anti-flag antibody (data not shown). After 24 h, cells with high expression levels were analyzed for HP1 localization and DAPI-stained heterochromatin domains.Immunofluorescent labeling, using mouse-anti-flag antibodies ( Figure 1) and rabbit-anti-flag (data not shown), showed that the transfected wild-type HP1␣-flag and HP1␤-flag proteins are targeted to the DAPI-intense stained heterochromatin domains in the nucleus, as shown also by others (Wreggett et al, 1994;Horsley et al, 1996;Minc et al, 1999;Cheutin et al, 2003). The same anti-flag antibodies showed that HP1␣-⌬(2-39)-flag and HP1␤-⌬(2-40)-flag proteins are localized in the nucleus.…”
supporting
confidence: 67%
“…Expression of all transfected proteins (full-length and truncated HP1) was detectable 12 h after transfection using an anti-flag antibody (data not shown). After 24 h, cells with high expression levels were analyzed for HP1 localization and DAPI-stained heterochromatin domains.Immunofluorescent labeling, using mouse-anti-flag antibodies ( Figure 1) and rabbit-anti-flag (data not shown), showed that the transfected wild-type HP1␣-flag and HP1␤-flag proteins are targeted to the DAPI-intense stained heterochromatin domains in the nucleus, as shown also by others (Wreggett et al, 1994;Horsley et al, 1996;Minc et al, 1999;Cheutin et al, 2003). The same anti-flag antibodies showed that HP1␣-⌬(2-39)-flag and HP1␤-⌬(2-40)-flag proteins are localized in the nucleus.…”
supporting
confidence: 67%
“…We further proceeded to investigate whether Udu is localized in the replicating pericentromeric heterochromatin by staining the cells for Udu or PAH-L and SANT-L domains and HP1␤, a marker for pericentromeric heterochromatin (Wreggett et al, 1994). Indeed, Udu (and PAH-LϩSANT-L) foci were colocalized with HP1␤ foci (Figure 5, T-W; data not shown).…”
Section: Udu Binds MCM Proteins and Localizes In Chromatin During Dnamentioning
confidence: 99%
“…1a, panel J), suggesting that GH promotes the relocalization of C/EBP␤ to areas of heterochromatin. To examine further the relocalization of C/EBP␤ to pericentromeric heterochromatin, heterochromatin protein 1-␣ (HP-1␣), a constitutive non-histone heterochromatin protein (33,34) was labeled with anti-HP-1␣ antibodies. HP-1␣ exhibits the same pattern of distribution as C/EBP␤ in cells treated with GH (Fig.…”
Section: Merging Of Immunofluorescense For C/ebp␤ (Panel A) and Dapmentioning
confidence: 99%